2020
DOI: 10.1016/j.vaccine.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of missed opportunities for vaccination (MOV) in Burkina Faso using the World Health Organization’s revised MOV strategy: Findings and strategic considerations to improve routine childhood immunization coverage

Abstract: Highlights We assessed reasons for missed opportunities for vaccination (MOV) in Burkina Faso. We found the prevalence of MOV was 76% among all eligible children. The prevalence of MOV was 97% among children attending for a non-vaccination visit. Health workers’ knowledge, attitude and practices were insufficient to minimize MOV. Reducing MOV can result in increases to both vaccine coverage and equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
(20 reference statements)
5
12
1
Order By: Relevance
“…Consistent with recent studies in low-income countries, 12 we found a higher MOV prevalence in children above 12 months. In a recent study that assessed MOV with WHO methodology in Chad and Malawi, Ogbuanu et al 13 found an MOV prevalence of 86% in Chad and 94% in Malawi among children above 1 year of age, compared with 49% and 61% below 1 year, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with recent studies in low-income countries, 12 we found a higher MOV prevalence in children above 12 months. In a recent study that assessed MOV with WHO methodology in Chad and Malawi, Ogbuanu et al 13 found an MOV prevalence of 86% in Chad and 94% in Malawi among children above 1 year of age, compared with 49% and 61% below 1 year, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a study in Haiti reported that up to 13% of reasons for undervaccination were child illness, despite the fact that mild infections should not prevent vaccination 25. A similar finding is highlighted in an MOV assessment in Timor-Leste, where Li et al 14 found that only 24% of healthcare workers were able to identify true contraindications, and Kaboré et al 12 reported that 83% of health workers failed to correctly identify valid contraindications for vaccination. This could be avoided through the proper adherence to the Integrated Management of Newborn and Childhood Illnesses guidelines,22 already in place in these countries 26…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, recent studies show that missed vaccination opportunities are most common when children attend for curative care. Thus, VCQI results only assess one component of the health system performance for vaccination [ 63 ]. Nonetheless, even without formal statistical tests or high-precision confidence intervals, broad-stroke results based on survey respondents with documented dates may suffice to inspire collaboration to address MOVs.…”
Section: Discussionmentioning
confidence: 99%
“…Catch-up vaccinations can also be given to children in contact healthcare facilities for acute or chronic illnesses. 19 There is growing evidence that the risk to benefit ratio is decidedly in favour of continuing vaccination services even when considering the consequences of doing so during the pandemic. 20 Gaining provider insights on effective strategies is essential to establishing context-specific mechanisms to prioritise catch-up for missed vaccines.…”
mentioning
confidence: 99%